BIBLIOMETRIC MAPPING OF STUDIES ON GREEN ACCOUNTING IN HEALTH - Ezgi Örs Günenç; İlknur Arslan Çilhoroz; Gülşen Çelik; Seyhan Çil Koçyiğit (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The aim of this study is to examine the structure of studies on green accounting in the field of health using the bibliometric technique of science mapping. Data were collected from the Web of Science database between 1945-2022 using 3 different search strategies. 59 publications were analyzed using VOSviewer and R-Studio software. The results showed that 2018 was the most effective year, although there was no steady increase in publication and citation trends. In both analyses, the keywords were clustered around environmental accounting. When the thematic map of the keywords was examined, it was seen that protection, environmental accounting, and externalities were the basic themes. In addition, the country which had the most citation in the field was the United States. Researchers who would like to study green accounting in the field of health should prioritize greenhouse gases, social and environmental accounting, green growth, and biodiversity, which are among the motor themes, in their studies.